Scope and effectiveness of equality plans - Marugán Pintos, Begoña (Sociología del Trabajo, 2021)
Organic Law 3/2007, for the effective equality of women and men, opened a new area for collective bargaining: equality plans. The objective of the equality plans was to eliminate labor discrimination and it represented a new area of union bargaining. However, the evaluation of equality plans has positive aspects, but also negative ones. This evaluation is made from the experience of 15 years in the negotiation of equality plans. R D. 901/2020, which regulates equality plans and their registration opens a new stage. For this reason, the evaluation is highly relevant.
Keywords: Equality plan; collective bargaining; unionism; sociology; feminisms; equality; social transformation